Selective spectrophotometric determination of fluoride in water samples using an Alizarin red S complex as a colored reagent - Prasuna, N.Vara; Kumar, R.Kishore; Damodharam, T. (IJRDO-Journal of Applied Science, 2015)
A simple, selective and sensitive spectrophotometric determination of fluoride in water samples has been developed using Alizarin red S-ZrOCl2 yellow colored complex. The method is based on the reaction of fluoride with the coloured complex .This method produces colourless complex resulting in the release of free ligands. The relationship of the reaction of fluoride with the complex is sixth-order polynomial function. The reaction reaches equilibrium at fluoride concentration of 0.054 mM. Beer-Lambert law is obeyed in the range 0.0 - 0.024 mM of fluoride (0.0 - 1.0 mg·L-1). The molar absorptivity at 502 nm is 6.45 × 103 L·mol-1·cm-1. The method was applied to determine the fluoride level under optimum conditions (pH 4.0, 25 oC). The recovery of fluoride in the range of 98.0-99.0% (SD: 1.12%) was successfully performed. The detection limit and quantitation limit were found to be 0.07 mg·L-1 and 0.2 mg·L-1 respectively. The proposed method was applied to determine trace amount of fluoride content in various water samples.